Pengaruh Polusi Udara Terhadap Pertumbuhan Dan Distribusi Lumut Di Beberapa Kampus Di Kota Medan - Faisal, Muhammad; Panggabean , Alimatusakdia; Wulandari , Dinda Riris; Dwi, Citra Partika; Azri, Riza Nazila; Syaputri, Aida Rizky (CV. ITTC INDONESIA, 2024)
This study analyzes the effect of air pollution on the growth and distribution of lichens in three campuses in Medan City, namely UIN Sumatera Utara, Universitas Negeri Medan, and Institut Teknologi Sawit Indonesia. Lichens are used as bioindicators of air quality because of their sensitivity to pollutants such as sulfur dioxide (SO₂) and nitrogen dioxide (NO₂). The study was conducted using a purposive sampling method with a path of 1 km at each observation location. The identification results showed the presence of eight types of lichens divided into two types, namely foliose and crustose. Foliose lichens are more often found in areas with good air quality, while crustose types are dominant in locations with higher pollution. This study confirms that air quality affects the diversity and distribution of lichens, making them an accurate bioindicator tool for monitoring air pollution.